A late Pleistocene human footprint from the Pilauco archaeological site, northern Patagonia, Chile - Moreno, Karen; Enrique Bostelmann, Juan; Macias, Cintia; Navarro-Harris, Ximena; De Pol Holz, Ricardo Hernán; Pino, Mario (My University, 2019)
The present study describes the discovery of a singular sedimentary structure corresponding to an ichnite that was excavated at the paleo-archaeological site Pilauco (Osorno, Chile). The trace fossil is associated with megafauna bones, plant material and unifacial lithic tools. Here we present a detailed analysis of the Pilauco ichnite and associated sedimentary structures, as well as new radiocarbon data. The ichnological analysis confidently assigns the trace to the ichnospecies Hominipes modernus-a hominoid footprint usually related to Homo sapiens. Some particular characteristics of the Pilauco trace include an elongated distal hallux, lateral digit impressions obliterated by the collapsed sediment, and sediment lumps inside and around the trace. In order to evaluate the origin of the ichnite, trackmaking experiments are performed on re-hydrated fossil bed sediments. The results demonstrate that a human agent could easily generate a footprint morphology equivalent to the sedimentary structure when walking on a saturated substrate. Based on the evidence, we conclude that the trackmaker might well have been a bare-footed adult human. This finding, along with the presence of lithic artifacts in the same sedimentary levels, might represent further evidence for a pre-Clovis South American colonization of northern Patagonia, as originally proposed for the nearby Monte Verde site.
Keywords: Homo sapiens; Megafauna; Footprint; Taphonomy; Neanderthal